Differences in Hemoglobin Levels 6 Hours and 24 Hours After Packed Red Cells Transfusion - Surawijaya Bakhtiar Kaslam; Usi Sukorini; Teguh Triyono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
The hemoglobin examination instructed by Dr. Sardjito General Hospital attending doctors was 6 hours after the PRC transfusion. It is recommended that a hemoglobin examination be carried out 24 hours after transfusion to determine the patient's hemoglobin after complete equilibrium occurs. This study aimed to determine the mean increase in Hb levels 6 hours and 24 hours after PRC transfusion and to examine the difference in Hb levels 6 hours and 24 hours after PRC transfusion, respectively, compared with baseline Hb levels in non-hematological malignancy patients. This prospective analytic observational study examined hemoglobin at 6 hours and 24 hours after PRC transfusion. The differential test between delta Hb levels 6 hours after PRC transfusion compared to baseline Hb levels and delta Hb levels 24 hours after PRC transfusion compared to baseline Hb levels were analyzed using paired T-test. There was a statistically significant difference between baseline Hb levels and Hb levels 6 hours after PRC transfusion (p<0.0001) and a statistically significant difference between baseline Hb levels and Hb levels 24 hours after PRC transfusion (p<0.0001). The differential test between delta Hb levels 6 hours after PRC transfusion compared to baseline Hb levels and delta Hb levels 24 hours after PRC transfusion compared to baseline Hb levels obtained a statistically significant difference (p=0.0024). The mean increase in hemoglobin was 1.76+0.78 g/dL 6 hours after PRC transfusion and 1.9+0.78 g/dL 24 hours after PRC transfusion. There were differences in delta Hb levels 6 hours and 24 hours after PRC transfusion, respectively, compared with baseline Hb levels in non-hematological malignancy patients, which were statistically significant but not clinically significant.